Principles of Arranging Independent Appraisal of Competences and Professional Development of Employees in Organization - K. V. Ekimova; S. M. Nechaeva; I. A. Kalinina (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The effective education system based on preliminary independent competence appraisal creates and supports conditions of continuous growth in professionalism of employees and provides involvement of each worker in his/her own professional improvement. The article discusses methodology of working out the program of independent employee appraisal, which includes several successive steps. An important component of the process is shaping the competence model proceeding from the content of professional standards, job profile and professiograms. Professional standards are selected in accordance with the current work of employees and job descriptions. The number of professional standards to devise management model depends on division functions for independent appraisal. On the basis of competence model a bank of tasks and questions is formed. The number of questions and their different complexity give an opportunity to split workers after testing into three or more groups of competence level. Thus, results of independent appraisal help project the employee’s profile and make decision concerning arrangement of training and selecting acute subjects. Preliminary independent appraisal of competence possession can provide efficient training of workers, which fosters the development of staff potential and sustainable functioning of then organization in general.